Answer:
508.68
*sorry if this is late
Step-by-step explanation:
Divide 36 by 2 to get radius
Multiply 18 by itself to get 324
Multiply 324 by 3.14 to get the area of a circle
Divide it by 2 to get the area of the semi circle
Answer:
Step-by-step explanation:
(f+g)(x) = 8x+2
(f-g)(x) = 4x-6
Step-by-step explanation:
Given
we have to find
<u>a. (f+g)(x)</u>
<u>b. (f-g)(x)</u>
Hence,
(f+g)(x) = 8x+2
(f-g)(x) = 4x-6
Keywords: Functions, Operations on Functions
Learn more about functions at:
#LearnwithBrainly
Step-by-step explanation:
4(a-3)=22
a-3=4-22
a-3=18
a=18+3
a=21
5(x-6)=65
x-6=65-5
x-6=60
×=60+6
x=66
hope it will help u...............